An empirical investigation on the factors that influence the use of audience response system - Mantikayan, Jonathan Mamangkiang; Abdullah, Lili Marziana; Ayu, Media Anugerah; Adamu, Abubakar Ibrahim; Abdulgani, Montadzah Ambag (Little Lion Scientific Islamabad Pakistan, 2014)

(untitled)
Majority of the earlier studies regarding the use of audience response systems have been devoted to higher educational level, with less attention given to secondary or high school level, and there is a dearth of research done on secondary education. To address the gap in the research literature, a study using quantitative survey has been used to explore and document the secondary students’ result outcomes on using the Audience Response System (ARS) vis-à-vis the traditional method, and to further explore if utilizing an ARS affects student performance outcome. In the end, the research examines the impact of ARS on student active learning, performance outcome and the task-technology fit of ARS in secondary level education. The major finding from this study shows that ARS add to a pre-existing active learning in secondary level education as well as the student’s performance. Above all, the task-technology fit affects the implementation of this system as regards the learning style of secondary school level.